Pelaksanaan Kegiatan Ekstrakurikuler Drumband Di SD Negeri 48 Ganting Padang - Mahendra Vaivi; Yensharti Yensharti (FBS Universitas Negeri Padang, 2020)
This study aims to determine and describe the implementation of drumband extracurricular activity in SDN 48 Ganting Padang. This type of research was qualitative research with using descriptive method including literature study, observation, interviews and documentation. The research instrument was the researcher. The Supporting instruments used were notebooks and stationery, photo cameras / mobile phones. This study explains that drumband is one of the extracurricular activities in SD Negeri 48 Ganting Padang. Drum Band is used to support flag ceremony. Besides, drumband is used by the community for babako parade events. Based on the results of the study, it is found that the implementation of the drumband begins by designing the principle of activity consisting of determining the participants of the exercise taken fromthe students at class VI, then determining the training time every Monday, Thursday, and Saturday. The material used namely marching exercises and musical exercises training that consisting of the song Indonesia Raya, Independence Day, Bangun Pemuda Pemudi, Bareh Solok, Ayam Den Lapeh, Malam Bainai and Moment of Silence. This extracurricular activitiy runs in accordance with the plans that have been made by the school.